An empirical investigation of going concern opinions: The influence of auditor reputation, leverage, and debt default - Ranti, Feby Krisda; Indriyanto, Erwin (Jurnal Akuntansi dan Manajemen, 2025)
This study examines the effect of auditors, leverage, and debt default on going-concern audit disclosures. Using a sample of 76 companies over the 2015–2019 period (380 observations), the study employs purposive sampling and data analysis using logistic regression analysis. The findings indicate that auditor reputation does not significantly affect going-concern opinions. As expected, leverage and debt default significantly increase the chances of receiving a going-concern opinion. In general, the findings of this study provide valuable insights for auditors, regulators, and corporate management to predict going-concern audit disclosures.